Automated swimming activity monitor for examining temporal patterns of toxicant effects on individual Daphnia magna. Issue 7 (21st July 2015) - Bahrndorff, Simon; Michaelsen, Thomas Yssing; Jensen, Anne; Marcussen, Laurits Faarup; Nielsen, Majken Elley; Roslev, Peter
Abstract: Aquatic pollutants are often biologically active at low concentrations and impact on biota in combination with other abiotic stressors. Traditional toxicity tests may not detect these effects, and there is a need for sensitive high‐throughput methods for detecting sublethal effects. We have evaluated an automated infra‐red (IR) light‐based monitor for recording the swimming activity of Daphnia magna to establish temporal patterns of toxicant effects on an individual level. Activity was recorded for 48 h and the sensitivity of the monitor was evaluated by exposing D. magna to the reference chemicals K2 Cr2 O7 at 15, 20 and 25 °C and 2, 4‐dichlorophenol at 20 °C. Significant effects ( P < 0.001) of toxicant concentrations, exposure time and incubation temperatures were observed. At 15 °C, the swimming activity remained unchanged for 48 h at sublethal concentrations of K2 Cr2 O7 whereas activity at 20 and 25 °C was more biphasic with decreases in activity occurring after 12–18 h. A similar biphasic pattern was observed after 2, 4‐dichlorophenol exposure at 20 °C. EC50 values for 2, 4‐dichlorophenol and K2 Cr2 O7 determined from automated recording of swimming activity showed increasing toxicity with time corresponding to decreases in EC50 of 0.03–0.07 mg l –1 h –1 . EC50 values determined after 48 h were comparable or lower than EC50 values based on visual inspection according to ISO 6341. The results demonstrated that the swimming activity monitor is capable of detecting sublethal behavioural effects that are toxicant and temperature dependent. The method allows EC values to be established at different time points and can serve as a high‐throughput screening tool in toxicity testing. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We have evaluated an automated monitor for recording the swimming activity of Daphnia magna to establish temporal patterns of toxicant and temperature effects. The sensitivity of the monitor was evaluated by exposing D. magna to K2 Cr2 O7 and 2, 4‐dichlorophenol. Significant effects of toxicant concentrations, exposure time and incubation temperatures were observed. The results demonstrated that the monitor is capable of detecting sublethal behavioural effects that are toxicant and temperature dependent and can serve as a high‐throughput screening tool in toxicity testing.